1994
DOI: 10.2307/1131404
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of School Outcomes Based on Early Language Production and Socioeconomic Factors

Abstract: Early differences in family SES, child language production, and IQ were related to outcomes in early elementary school in the present prospective, 10-year longitudinal study. In a prior study of family interactional variables associated with language learning, major differences in parenting (i.e., time, attention, and talking) were found to be associated with differences in child productive vocabulary between 7 to 36 months of age, and child IQ, favoring higher-SES parents. Lower-SES children were exposed less… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
321
2
15

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 565 publications
(361 citation statements)
references
References 24 publications
23
321
2
15
Order By: Relevance
“…This income is almost 150% of the median annual household income in 2011 of $50,054 as detailed by the United States Census Bureau statistics (27). However, it has been described previously that low socioeconomic status alone may be causal in speech/language and cognitive impairments (28). In the present study, socioeconomic status did not appear to confound the results because the sample population was relatively affluent and Caucasian.…”
Section: Discussionmentioning
confidence: 46%
“…This income is almost 150% of the median annual household income in 2011 of $50,054 as detailed by the United States Census Bureau statistics (27). However, it has been described previously that low socioeconomic status alone may be causal in speech/language and cognitive impairments (28). In the present study, socioeconomic status did not appear to confound the results because the sample population was relatively affluent and Caucasian.…”
Section: Discussionmentioning
confidence: 46%
“…La Paro and Pianta (2000) found a moderate effect size (.49) across more than 60 studies predicting academic achievement from kindergarten through second grade from early cognitive skills including preschool language development. Similarly, others have found that early language performance is an important predictor of later reading, spelling and language, independent of socioeconomic status, and such predictions remain stable during early elementary school years (Walker, Greenwood, Hart, & Carta, 1994). Recently, in a large normative sample, the NICHD Early Child Research Network (2005) demonstrated that preschool oral language operated both directly and indirectly on first and third grade outcomes.…”
Section: Introduction: Early Language and Emerging Literacymentioning
confidence: 94%
“…Recently, in a large normative sample, the NICHD Early Child Research Network (2005) demonstrated that preschool oral language operated both directly and indirectly on first and third grade outcomes. Specifically, scores on the 54 month Preschool Language Scale (PLS; Zimmerman, Steiner, & Booth, 1995;Thomasgard & Shonkoff, 1993;Walker et al, 1994). Much of the impact of young motherhood on the child is mediated by multiple factors associated with socioeconomic status (Kinard & Klerman, 1983), especially maternal education (Kinard & Reinherz, 1984) and mothers' cognitive achievement (Moore & Snyder, 1991).…”
Section: Introduction: Early Language and Emerging Literacymentioning
confidence: 99%
“…The PARCA3 has been designed to assess toddlers' non-verbal cognitive skills. However, because verbal abilities are a crucial component of cognitive abilities and intelligence (16) , parents were asked to complete an assessment of children's verbal and communicative skills in addition to the PARCA3. The verbal abilities assessment tool was the shortened British version of the MacArthur Communicative Development Inventory-III (CDI-III (17) ) .…”
Section: Introductionmentioning
confidence: 99%